Rural–urban differentials in the factors associated with knowledge on and acceptance of the COVID-19 vaccine in the second wave of the pandemic among adults in Northern Ghana - Yula Salifu; Joseph Lasong; Ruth Nimota Nukpezah; Joachim Masawud Mbemah; Mubaric Yakubu; Torjim Salifu (Discover Public Health)
Abstract Background The second wave of the COVID-19 pandemic in Africa revealed the need for advancements towards COVID-19 preventive measures such as vaccination to control its spread. Thus, this paper highlighted the underlying rural–urban differentials in the factors associated with knowledge on and acceptance of the COVID-19 vaccine in the second wave of the pandemic among adults in Northern Ghana. Methods A community-based cross-sectional design following a systematic sampling procedure was used to sample 437 adults who met the study’s inclusion from May to November 2021 in Northern Ghana. A multivariable binary logistic regression model was used to identify key determinants of knowledge on and acceptability of COVID-19 vaccine. Results In urban vs rural residents, COVID-19 vaccine knowledge and acceptance rates were 72.63% vs 30.26% and 57.54% vs 20.39% accordingly. Across both residencies, unemployed persons had lower odds of COVID-19 vaccine acceptance. In urban vs rural settings, females’ vs those with tertiary education had lower and higher odds of COVID-19 vaccine acceptance respectively. Across both residencies, unemployed persons and those willing to accept the vaccine had higher and lower odds of having low COVID-19 vaccine knowledge respectively. In urban settings, those aged 41–45 years had lower odds of having low COVID-19 vaccine knowledge. Conclusions Generally, vaccine knowledge and acceptability were low, but higher among urban than rural residents. Thus, targeted health promotion and education campaigns should aim to improve vaccine knowledge. Further, enhancing the perceived benefits of COVID-19 vaccination and advocating for vaccination could boost vaccine acceptance.